Caracterização morfométrica da Bacia Ribeirão Ponte Alta, Bofete - SP - CORTEZ, JÚLIA RINALDI DE MACEDO (2024)
This work aims to analyze the physiographic characteristics of the Ribeirão Ponte Alta Basin, highlighting its importance based on morphometric studies of the basin, which bring the dynamics of the river basin in its natural state, with analysis of the morphostructural influence on the drainage network and identify possible structural constraints on the relief. The applied parameters address the shape factor (Kf); compactness coefficient (Kc); circularity index (Ic); drainage network frequency (Dr); sinuosity of the main river (Sin); drainage density (Dd); texture ratio (T); average slope of the basin (H); relief ratio (Rr); elongation ratio (Re), average surface runoff extension (l) and finally, the roughness index (Ir), providing an overview of the main geometric and drainage parameters used in this process. Finally, possible challenges and opportunities related to the sustainable management of the Ribeirão Ponte Alta Basin will be discussed.